1969
DOI: 10.1002/oms.1210020502
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry of methyltetrazoles

Abstract: Abstract-The m a s spectra of tetrazole, al1 isomers of mononiethyl-and dimethyltetrazole, several trifluoromethyl substituted tetrazoles, as well as deuterated analogs, were recorded. Loss of N, was the important fragmentation of the molecular ions of tetrazole and 2-niethyl substituted tetrazoles; however, HN2 loss was more important for 1-methyl substituted tetrazoles. The l-methyltetrazoles showed molecular ion peaks while the 2-methyltetrazoles exhibited an unprecedented [M + 11 peak with no molecular ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…The structures of all intermediates and retinals were ascertained by NMR, UV and MS measurements. The 9-cis *The position of methylation was determined by ELMS according to Forkey and Carpenter (1969). isomers were used for binding studies with bovine opsin whereas the all-trans isomers were used for the formation of bR analogs.…”
Section: Methodsmentioning
confidence: 99%
“…The structures of all intermediates and retinals were ascertained by NMR, UV and MS measurements. The 9-cis *The position of methylation was determined by ELMS according to Forkey and Carpenter (1969). isomers were used for binding studies with bovine opsin whereas the all-trans isomers were used for the formation of bR analogs.…”
Section: Methodsmentioning
confidence: 99%
“…Substituted diazirine ions were also reported as the major fragment ions in the EI fragmentation of substituted tri-and tetrazoles. [18][19][20] Only the spectrum of 6 does not contain ion c but the presence of ion [c…”
Section: -Thionesmentioning
confidence: 99%
“…N 2 elimination was also shown to be the preferential primary fragmentation process during studies conducted by Fischer et al and Shurukhin et al, on 5-(1-acyl-2-dialkylaminovinyl)-1-aryl-1H-tetrazoles and 1-( o -, m -, and p -tolyl)-5-phenyltetrazoles, respectively [ 23 , 24 ]. Nevertheless, although some important features are frequently retained, one important conclusion to withhold is that electron ionization-induced cleavages in this class of compounds are highly dependent upon the nature of the substituents [ 22 , 23 , 25 , 26 ]. In parallel, studies on the photochemistry of some substituted tetrazoles have shown that the preferential structures formed from photocleavage are azides, aziridines and isocyanates, with the nature of the substituents attached to the tetrazole ring strongly influencing the fate of photoreactions, whether due to their chemical nature, the possibility of cross-reactions or conformational impairments [ 16 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%